SCIENTIFIC WORK DISSEMINATION IN INDONESIA: A PILOT STUDY - Setio Devi, Katrin; Rahmi, Rahmi; Triasih, Hermin (BACA: Jurnal Dokumentasi dan Informasi, 2020)
This article describes the research dissemination activities of lecturers and researchers in Indonesia. Data were collected through an online survey with 39 questions distributed to respondents via social media from 21 to 31 July 2020. Thirty out of 77 respondents completed the online questionnaire. The results identified variables, such as resources available for dissemination, planning and targeting dissemination activity, evaluating the effects, and capturing research influence. The results revealed that almost all respondents realised the importance of dissemination and wanted to participate. The results show that 80% dissemination activities are conducted through academic journals. Assistance and instruction from specialize divisions or institutions are needed for the dissemination process so that results are maximally employed and so that the role of research is increased in policymaking. Although only 3 % researchers evaluated their research, when asked about the influence of their research, most researchers provided examples of the influence of their research. Researchers understand the importance of dissemination and have been putting it into practice. Researchers require clear guidance from institutions that can assist them in the dissemination process from the planning stage to dissemination.